2000
DOI: 10.1021/jp992379l
|View full text |Cite
|
Sign up to set email alerts
|

Triplet Radical Interaction. Direct Measurement of Triplet Polarization Transfer by Fourier Transform Electron Paramagnetic Resonance

Abstract: An FT-EPR (Fourier transform electron paramagnetic resonance) method for the direct measurement of the electron spin polarization generated in stable radicals through photoexcited triplet and radical interaction is presented. This method depends on the ability to calculate numerically the filling factor of the irradiated volume in the EPR cavity. By this experimental method the polarization at different times after the laser pulse can be determined. This enables us to differentiate between the different proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 30 publications
2
38
0
Order By: Relevance
“…Several mechanisms have been described in the literature by which nonequilibrium spin polarization resulting from photoexcitation can be transferred to a stable radical. In the RP mechanism, the radical is polarized as a result of spin-selective recombination of the RP, and localized triplet states resulting from charge recombination do not play a role. , In the radical–triplet pair mechanism (RTPM), the electron spin polarization transfer (ESPT) mechanism, and the reversed quartet mechanism (RQM), strong interactions between the radical and a localized triplet state (which may arise from RP charge recombination or spin orbit induced intersystem crossing) lead to polarization. ,, Finally, EISC in systems with weak coupling between the radical and triplet species has been proposed to directly polarize the radical . Both charge recombination and 3* ANI decay in 1b at room temperature proceed more quickly than the instrument response time of the EPR experiment, meaning it is not possible to correlate the growth of polarization with kinetics obtained from optical spectroscopy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several mechanisms have been described in the literature by which nonequilibrium spin polarization resulting from photoexcitation can be transferred to a stable radical. In the RP mechanism, the radical is polarized as a result of spin-selective recombination of the RP, and localized triplet states resulting from charge recombination do not play a role. , In the radical–triplet pair mechanism (RTPM), the electron spin polarization transfer (ESPT) mechanism, and the reversed quartet mechanism (RQM), strong interactions between the radical and a localized triplet state (which may arise from RP charge recombination or spin orbit induced intersystem crossing) lead to polarization. ,, Finally, EISC in systems with weak coupling between the radical and triplet species has been proposed to directly polarize the radical . Both charge recombination and 3* ANI decay in 1b at room temperature proceed more quickly than the instrument response time of the EPR experiment, meaning it is not possible to correlate the growth of polarization with kinetics obtained from optical spectroscopy.…”
Section: Discussionmentioning
confidence: 99%
“…16,40 In the radical−triplet pair mechanism (RTPM), the electron spin polarization transfer (ESPT) mechanism, and the reversed quartet mechanism (RQM), strong interactions between the radical and a localized triplet state (which may arise from RP charge recombination or spin orbit induced intersystem crossing) lead to polarization. 65,72,73 Finally, EISC in systems with weak coupling between the radical and triplet species has been proposed to directly polarize the radical. 63 Both charge recombination and 3 *ANI decay in 1b at room temperature proceed more quickly than the instrument response time of the EPR experiment, meaning it is not possible to correlate the growth of polarization with kinetics obtained from optical spectroscopy.…”
Section: ■ Discussionmentioning
confidence: 99%
“…The latter approach was used here, with all parameters taken from ref 18, giving P n = −108 P eq . An additional hyperfine dependent polarization term P m may be included in equation 20 to account for generation of multiplet polarization, 38 but it has been experimentally demonstrated that only net polarization is significant for the xanthenenitroxide systems discussed here. 18 The expectation values of the electron and nuclear magnetization in the 4-level system take their familiar form representing the population differences,…”
Section: Please Cite This Article As Doi:101063/15133408mentioning
confidence: 99%
“…We consider how these are affected by the illumination pulse length and duty cycle, beginning with comparison to the effects reported for pulsed microwave DNP by Vieth and co-workers. 20,21 They derived an expression for the overall enhancement under pulsed microwave irradiation: (38) where φ is the flip angle, = e 1 p , with p and d pulse and delay length respectively, B 1 the microwave field strength and s max is a maximum saturation factor dependent on the number of hyperfine lines subject to on-resonance irradiation. This results in two components to the pulse length dependence of the enhancement:…”
Section: Please Cite This Article As Doi:101063/15133408mentioning
confidence: 99%
“…We can summarize the reactions involved in the interaction of a photoexcited triplet and a stable radical by extending the earlier [43] reaction scheme into:…”
Section: Radical-photoinduced Triplet Interaction the Radical-tripletmentioning
confidence: 99%